2018
DOI: 10.1177/1533317518782173
|View full text |Cite
|
Sign up to set email alerts
|

Body Composition, Dietary, and Gustatory Function Assessment in People With Alzheimer’s Disease

Abstract: Patients with AD show worst outcomes in terms of anthropometric measurements, lifestyle habits (diet, exercise), and gustatory function than controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…So far, the association between these two dietary patterns and AD remains controversial. Several studies demonstrated that Mediterranean diet and MIND diet contributed to the cognitive function of AD patients as well as old adults ( 43 , 44 ). For example, a parallel-group randomized clinical trial of 447 cognitively healthy subjects from Spain (mean age 66.9 years) found that Mediterranean diet improved cognitive function of subjects ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…So far, the association between these two dietary patterns and AD remains controversial. Several studies demonstrated that Mediterranean diet and MIND diet contributed to the cognitive function of AD patients as well as old adults ( 43 , 44 ). For example, a parallel-group randomized clinical trial of 447 cognitively healthy subjects from Spain (mean age 66.9 years) found that Mediterranean diet improved cognitive function of subjects ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…Such cases include people who have Alzheimer’s disease. The onset of malnutrition in those people is a common phenomenon and contributes to the acceleration of disease progression [ 33 , 34 ]. Malnutrition, in their case, is affected, not only by age-related changes, but also by the disease itself.…”
Section: Nutrition In the Prevention And Alzheimer’s Diseasementioning
confidence: 99%
“…It has also been proven that these people are more likely to experience a decrease in taste function, contributing to a reduction in the number of meals consumed [ 33 ]. An important aspect in their case is also a change in eating habits.…”
Section: Nutrition In the Prevention And Alzheimer’s Diseasementioning
confidence: 99%
“…5 Accordingly, increased WC is a risk factor for metabolic and related disorders including diabetes, hypertension, and coronary artery disease independent of overall adiposity levels, 6 and studies suggest that it may more accurately identify individuals at particularly high diabetes and cardiovascular disease risk than traditional measures of adiposity-like body mass index (BMI). 7,8 Furthermore, increased WC may also have adverse effects on the brain in otherwise healthy people and in those with other neurologic diseases besides MS. 9,10 For example, increasing WC correlates with lower gray matter volumes in the general population and predicts more rapid future cognitive decline among individuals with Alzheimer’s disease irrespective of overall adiposity level. 9,10…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Furthermore, increased WC may also have adverse effects on the brain in otherwise healthy people and in those with other neurologic diseases besides MS. 9,10 For example, increasing WC correlates with lower gray matter volumes in the general population and predicts more rapid future cognitive decline among individuals with Alzheimer’s disease irrespective of overall adiposity level. 9,10…”
Section: Introductionmentioning
confidence: 99%